2008
DOI: 10.1055/s-2008-1076747
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer: Preoperative Pulmonary Evaluation of the Lung Resection Candidate

Abstract: Lung resection provides the best chance of cure for individuals with early-stage non-small-cell lung cancer. Lung resection will lead to a decrease in lung function. The population that develops lung cancer often has concomitant lung disease and a reduced ability to tolerate further losses in lung function. The goal of the preoperative pulmonary assessment of individuals with resectable lung cancer is to identify those individuals whose short- and long-term morbidity and mortality would be unacceptably high if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 121 publications
(158 reference statements)
0
5
0
Order By: Relevance
“…Otherwise, evaluation of residual lung function should be performed [14,15]. In our study, all patients' FEV 1 values were less than the threshold values (2.0 l for pneumonectomy or 1.5 l for lobectomy).…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, evaluation of residual lung function should be performed [14,15]. In our study, all patients' FEV 1 values were less than the threshold values (2.0 l for pneumonectomy or 1.5 l for lobectomy).…”
Section: Discussionmentioning
confidence: 99%
“…The prediction of postoperative lung function is mandatory in the preoperative evaluation of lung cancer patients, especially in those with reduced lung function (14). The current standard for predicting postoperative lung function uses spirometry, such as forced expiratory volume in one second, and diffusing capacity of the lung for carbon monoxide or radionuclide lung scanning (15). In much earlier research, Wu et al (16) used quantitative CT and found that it correlated well with postoperative lung function in patients with lung cancer.…”
Section: Quantification Of Severity In Diffuse Lung Diseasementioning
confidence: 99%
“…Prediction of postoperative lung function plays a key role in the preoperative evaluation of lung cancer patients with impaired lung function in order to identify an increased risk of postoperative complication and mortality [43]. Currently, postoperative lung function is predicted using spirometry, including forced expiratory volume in 1 s and diffusing capacity for carbon monoxide, and radionuclide lung scanning [44]. An accurate prediction of postoperative pulmonary function is considered for conditions with inhomogeneous effective pulmonary function such as pulmonary emphysema or interstitial lung disease (ILD) [45].…”
Section: Prediction Of Postoperative Lung Function or Postoperative Mmentioning
confidence: 99%